A Cunhã Coletivo Feminista: subjetividade, história e feminismo na Paraíba (1990-2015) - Sobreira, Dayane Nascimento (2017)
The state of Paraíba has a long trajectory when it comes to the struggle of women, who, for a long time, have been absent from history. This paper aims to clarify the trajectory of the NGO Cunhã Coletivo Feminista, highlighting their protagonism in the fight for rights and for gender equality in the state. Founded in 1990, the NGO was born as a development of previous feminist groups and has outstanding action with urban and rural women from Paraíba‟s coastal, Agreste and Cariri areas. Using oral history methodology, we connected the life histories of the NGO members, in a close relationship between a history that was made and that is being made, and memory. We also utilized texts, projects, reports, brochures, guidebooks and other materials essential to those histories. We will observe the creation of new subjectivation practices and the consolidation of an institutionalized feminism that originated other groups and movements and was essential to network building, the consolidation of connections and the dialogue with regional and national feminism. Thus, we hope to contribute to the history and memory of the NGO at the same time that we bring forth the members‟ life histories and trace a history of the feminine protagonism, the resistances and the feminist movement in Paraíba.